2021
DOI: 10.1039/d1cy01081f
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the effects of individual components in KxMnOy/SiO2and water on selectivity enhancement in the oxidative coupling of methane

Abstract: Until now a great number of various materials have been tested for the oxidative coupling of methane (OCM). On the basis of previous statistical analysis of OCM-related literature data, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…11−13 Very recently, we have demonstrated that the selectivity over other catalysts can also be enhanced through cofed water. 14,15 Our mechanistic and kinetic analysis suggests that the improvement should be due to H 2 O-assisted decomposition of surface biatomic oxygen species responsible for CO 2 formation.…”
Section: ■ Introductionmentioning
confidence: 92%
“…11−13 Very recently, we have demonstrated that the selectivity over other catalysts can also be enhanced through cofed water. 14,15 Our mechanistic and kinetic analysis suggests that the improvement should be due to H 2 O-assisted decomposition of surface biatomic oxygen species responsible for CO 2 formation.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Because such multiple synergy is expected to occur only slightly when using a conventional method, this new finding is anticipated as a predominant protocol for ML-aided catalyst investigation. Moreover, the role of Mn still remains an open question in OCM studies. ,, For instance, there has been reports on not only the positive effect in Mn-Na 2 WO 4 /SiO 2 and K x MnO y /SiO 2 but also the negative effect in the La 2 O 3 - or MgO-based catalyst . Because under the OCM the following occur: (i) C 2 production is influenced not only via the surface of catalyst but also via the outer surfaces (gas-phase) reaction. (ii) The reaction usually performs under a high reaction temperature above melting points of metal components. (iii) Synergy of components might be different from kinds of support, ,, and the effect of Mn in OCM under operation conditions is still a controversial subject.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the role of Mn still remains an open question in OCM studies. ,, For instance, there has been reports on not only the positive effect in Mn-Na 2 WO 4 /SiO 2 and K x MnO y /SiO 2 but also the negative effect in the La 2 O 3 - or MgO-based catalyst . Because under the OCM the following occur: (i) C 2 production is influenced not only via the surface of catalyst but also via the outer surfaces (gas-phase) reaction. (ii) The reaction usually performs under a high reaction temperature above melting points of metal components. (iii) Synergy of components might be different from kinds of support, ,, and the effect of Mn in OCM under operation conditions is still a controversial subject. In other words, it is demonstrated that the HTS data-driven ML approach can aid catalyst investigation without scientists’ experiences and discover the positive fourth element (viz.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations